2011
DOI: 10.1002/we.503
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control for wind turbines with distributed active flaps: incorporating inflow signals and actuator constraints

Abstract: This paper describes the implementation of system identification and controller design techniques using model predictive control (MPC) for wind turbines with distributed active flaps for load control. An aeroservoelastic model of the 5 MW NREL/Upwind reference wind turbine, implemented in the code DU_SWAMP, is used in an industry-based MPC controller design cycle, involving the use of dedicated system identification techniques. The novel multiple-input multiple-output MPC controllers, which incorporate flap ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 30 publications
1
69
0
Order By: Relevance
“…The control configuration based on only measurements feedback (d 00) lowers the lifetime fatigue equivalent damage on the blade root flapwise bending moment by about 10 %, a result in line with previous investigations that considered similar setups [12,17]. Periodic load anticipation, which is based on the blade azimuthal position and handled by the LQ algorithm as a prediction on periodic disturbance signals, allows to reach higher lifetime damage alleviation: 13. pation is comparable to the increase previous investigations have attained using additional in-flow sensors [12,14], with the advantage that the periodic load anticipation approach does not require a sensor setup as complicate and delicate as demanded for in-flow measurements. As an effect of active load alleviation with adaptive trailing edge flaps, a significant increase of the blade torsion fatigue damage equivalent load is reported (nearly 10 %); the increase of the torsional loads, and, to a lesser extent, of loads on other components, should be hence taken into account in the design of smart rotor structures.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…The control configuration based on only measurements feedback (d 00) lowers the lifetime fatigue equivalent damage on the blade root flapwise bending moment by about 10 %, a result in line with previous investigations that considered similar setups [12,17]. Periodic load anticipation, which is based on the blade azimuthal position and handled by the LQ algorithm as a prediction on periodic disturbance signals, allows to reach higher lifetime damage alleviation: 13. pation is comparable to the increase previous investigations have attained using additional in-flow sensors [12,14], with the advantage that the periodic load anticipation approach does not require a sensor setup as complicate and delicate as demanded for in-flow measurements. As an effect of active load alleviation with adaptive trailing edge flaps, a significant increase of the blade torsion fatigue damage equivalent load is reported (nearly 10 %); the increase of the torsional loads, and, to a lesser extent, of loads on other components, should be hence taken into account in the design of smart rotor structures.…”
Section: Resultssupporting
confidence: 67%
“…All the investigations confirmed that smart rotors with trailing edge flaps have a potential for reducing the fatigue loads experienced by the turbine; nevertheless, they reported rather widespread results, with load reductions figures ranging from 5 to 47 percent, see the summary compiled by Barlas et al [12]. Differences in the alleviation performances can originate from several sources: the models used in the aeroelastic simulations, the conditions of the wind field and its turbulence levels, the maximum deflection and extension of the flap actuators, and also the choices made in designing the flap control system, as the assumptions on the available sensors and measurements, and the type of control algorithm implemented.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations